Analisa Minat Beli Konsumen Platform Shopee Perbandingan Batam dan Bandung dengan TAM - Ng, Jackson; Eryc, Eryc; Tjahyadi, Surya (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
With the increasing number of internet users in Indonesia has brought significant changes at trade sector. This reflected changes in conventional trading to electronic trading. With the increasing number of business actors in this sector, the conditions in the market are also becoming more competitive. So, it cannot be denied that there is the potential for unhealthy competition in the e-commerce sector and makes users hesitate to carry out transactions on this platform. Therefore, in this research an analysis will be carried out regarding consumer perceptions of making online purchase transactions on one of the giant e-commerce companies in Indonesia, namely Shopee. The aim of this research is to analyze the factors that influence someone to carry out a transaction using e-commerce technology. This research was carried out quantitatively by distributing questionnaires online and responded by 385 respondents from the cities of Batam and Bandung. The research analysis method was carried out with the help of SPSS and AMOS applications with the SEM-AMOS approach to analyze data. The research results concluded that for both the cities of Batam and Bandung, all the variables contained in the TAM model positively influence a person's buying interest at Shopee.